A phase I trial of the human double minute 2 inhibitor (MK-8242) in patients with refractory/recurrent acute myelogenous leukemia (AML). (September 2016) - Ravandi, Farhad; Gojo, Ivana; Patnaik, Mrinal M.; Minden, Mark D.; Kantarjian, Hagop; Johnson-Levonas, Amy O.; Fancourt, Craig; Lam, Raymond; Jones, Mary Beth; Knox, Clayton D.; Rose, Shelonitda; Patel, Payal Shah; et al.
Highlights: This study evaluated MK-8242 in subjects with wild type p53 refractory/recurrent AML. Adequate safety was seen at doses ≤300 mg BID using 7-day on/14-day off dosing. Observed dose-related toxicities included gastrointestinal and hematologic AEs. An MTD and RP2D were not established for 7-day on/14-day off dosing schedule. Single agent clinical activity was observed in this study. Abstract: Objective: Evaluate safety/tolerability/efficacy of MK-8242 in subjects with refractory/recurrent AML. Methods: MK-8242 was dosed p.o. QD (30–250 mg) or BID (120–250 mg) for 7on/7off in 28-day cycle. Dosing was modified to 7on/14off, in 21-day cycle (210 or 300 mg BID). Results: 26 subjects enrolled (24 evaluable for response); 5/26 discontinued due to AEs. There were 7 deaths; 1 (fungal pneumonia due to marrow aplasia) possibly drug-related. With the 7on/7off regimen, 2 subjects had DLTs in the 250 mg BID group (both bone marrow failure and prolonged cytopenia). With the 7on/14off, no DLTs were observed in 210 mg BID or 300 mg BID (doses >300 mg not tested). Best responses were: 1/24 PR (11 weeks;120 mg QD, 7on/7off); 1/24 CRi (2 weeks;210 mg BID, 7on/14off); 1/24 morphologic leukemia-free state (4 weeks; 250 mg BID, 7on/7off). PK on Day7 at 210 mg BID revealed AUC0–12 h 8.7 μM·h,  Cmax 1.5 μM (n = 5,  Tmax, 2–6 h),  T1/2 7.9 h, CLss /F 28.8 L/h, and Vss /F 317 L. Conclusions: The 7on/14off regimen showed a more favorable safety profile; no MTD was established. Efficacy was seen using both regimens providing impetus for further study of HDM2 inhibitors in subjects with AML.